Literasi Informasi dalam Pembayaran Zakat Digital Melalui Aplikasi KitaBisa di Desa Payakabung, Indralaya Utara, Ogan Ilir - Dani, Riki Walian; Rukmana, Ceriah; Vlora, Rani Kurnia; Fitri, Emilia (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Information literacy has an important role in developing digital zakat payments, especially through the KitaBisa application. This service research was conducted in Payakabung Village, North Indralaya, Ogan Ilir, with the main aim of increasing information literacy related to digital zakat payments among the community. The service method used includes direct counseling to the Payakabung Village community in using the KitaBisa application to pay zakat. The results of the service show a significant increase in the community's understanding and skills regarding digital zakat payments through the KitaBisa application. Apart from that, community participation in paying zakat via digital methods has also increased, reflecting the success of this service activity in increasing information literacy and the use of technology in religious practices. Thus, this service activity succeeded in making a positive contribution by expanding access and speeding up the zakat payment process, as well as increasing efficiency in managing zakat funds in Payakabung Village, North Indralaya, Ogan Ilir.